REACTION STOICHIOMETRY IN THE SYNTHESIS OF HYDROCARBONS BY THE FISHER-TROPSCH METHOD - Suxrob Ro’ziyev (Web of Journals Publishing, 2024)
The synthesis of hydrocarbons from CO and H2 in the Fischer-Tropsch method is a complex system of chemical reactions that take place in series and in parallel with the presence of a catalyst.